A method for preparing a drug sustained-release coating on the surface of a zinc alloy implant

By preparing a multifunctional drug sustained-release coating on the surface of zinc alloy implants, the problem of zinc alloy vascular stent triggering inflammatory response and restenosis during implantation is solved, and the comprehensive effects of biocompatibility, antibacteriality and drug sustained-release are achieved.

CN117547655BActive Publication Date: 2025-03-18SHANDONG INST OF ADVANCED TECH CHINESE ACAD OF SCI CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311496739.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-10
Publication Date
2025-03-18
Estimated Expiration
2043-11-10

AI Technical Summary

Technical Problem

Existing zinc alloy vascular stents are prone to induce inflammatory responses, restenosis and secondary thrombosis during implantation, resulting in implant failure and lack effective antibacterial and drug sustained release solutions.

Method used

Through surface cleaning, oxidation, a multifunctional drug sustained-release coating is prepared on the surface of zinc alloy implants, combined with a silane coating to slow drug release and degradation.

Benefits of technology

It improves the biocompatibility and antibacterial properties of zinc alloy implants, realizes the drug sustained release function, slows down the degradation rate of implants, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GHA0000008964730000071
    Figure GHA0000008964730000071
  • Figure GHA0000008964730000081
    Figure GHA0000008964730000081
Patent Text Reader

Abstract

The present invention belongs to the field of medical devices, and provides a method for preparing a drug sustained-release coating on the surface of a zinc alloy implant, comprising: cleaning the surface of a zinc-based material, placing it in a salt solution, and oxidizing it; immersing the oxidized zinc-based material in a 3-aminopropyltrimethoxysilane or polyethyleneimine solution to obtain an aminated zinc-based material; alternately immersing the aminated zinc-based material in a solution with positively and negatively charged molecules for multiple times to obtain a zinc-based material with an assembled coating; immersing the zinc-based material with an assembled coating in a silane solution. The present invention is simple to prepare, low in cost, degradable, and can satisfy antibacterial and drug sustained-release functions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of medical devices, and particularly relates to a method for preparing a drug sustained-release coating on the surface of a zinc alloy implant. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Cardiovascular disease has become one of the diseases with the highest mortality rate worldwide. It is reported that the prevalence of cardiovascular disease has been on the rise, and the mortality rate is higher than that of tumors and other diseases. Vascular stent implantation is one of the commonly used interventional treatment methods. Stents can support blood vessels, reduce vascular elastic retraction, and maintain smooth blood flow in the lumen, becoming the first choice for treating severe cardiovascular blockage. In the initial clinical treatment, bare metal stents and drug-eluting stents are usually inert metals, such as nickel-titanium alloys and medical stainless steel. Long-term presence in blood vessels can cause inflammatory reactions, and later it is easy to cause restenosis and secondary thrombosis in blood vessels, leading to implantation failure. The emergence of biodegradable stents is hailed as the "fourth revolution" of vascular stents. During vascular reconstruction, degradable stents will be absorbed or metabolized by the body at an appropriate rate and will not cause local and systemic toxicity. Degradable metal magnesium was first tested for cardiovascular stents, and then iron and its alloys were also widely tested. Studies have shown that the corrosion rate of iron-based alloys is too slow, the degradation products are difficult to be absorbed by tissue metabolism, and the ferromagnetism interferes with magnetic resonance imaging; magnesium and its alloys degrade too quickly, which will shorten the service life of the stent. In recent years, zinc and its alloys have received increasing attention as a new generation of biodegradable metals. Zinc is one of the trace elements of the human body and is involved in a variety of physiological activities. Compared with iron and magnesium, zinc-based alloys have a more suitable degradation rate and are considered to be promising bioresorbable vascular stent materials. During the implantation process, the stent may damage the blood vessel wall, contact endothelial cells, smooth muscle cells and blood, and easily cause inflammatory reactions, stent stenosis and other problems. Therefore, the biocompatibility of zinc alloys needs to be improved in the early implantation stage.

[0004] The biocompatibility of materials is closely related to their surface properties. Surface modification technology can simply and effectively improve the biocompatibility of zinc alloy surfaces and promote tissue healing. Organic molecules, inorganic particles and functional drugs can be combined with the alloy surface through surface modification and coating preparation to improve the corrosion resistance, antibacterial properties and biocompatibility of the alloy. During the slow degradation of the coating, the drug sustained release function is satisfied at the same time, and the degradation of the alloy itself is not affected. At present, there is no better solution for the surface modification and coating preparation of medical zinc alloy stents. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a method for preparing a drug sustained-release coating on the surface of a zinc alloy implant. The present invention provides a method for preparing a degradable multifunctional coating on the surface of a zinc alloy that is simple to prepare, low in cost, degradable, and can satisfy the functions of antibacterial and drug sustained-release.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] The first aspect of the present invention provides a method for preparing a drug sustained-release coating on the surface of a zinc alloy implant, comprising:

[0008] The zinc-based material is surface cleaned and placed in a salt solution for oxidation;

[0009] The oxidized zinc-based material is immersed in a 3-aminopropyltrimethoxysilane or polyethyleneimine solution to obtain an amino-modified zinc-based material;

[0010] The aminated zinc-based material is alternately immersed in solutions with positively charged and negatively charged molecules for multiple times to obtain a zinc-based material with an assembled coating;

[0011] The zinc-based material with the assembly coating is immersed in a silane solution to obtain;

[0012] Wherein, the positively charged molecule is at least one of chitosan, polyethyleneimine, polyurethane, lysine, and arginine;

[0013] The negatively charged molecule is at least one of silk fibroin, polypeptide, sodium hyaluronate, sodium alginate, polyacrylic acid and drugs.

[0014] In some embodiments, the salt solution is a NaCl solution with a mass fraction of 0.9% to 1.2%. The surface oxidation treatment is to make the sample surface have hydroxyl groups -OH so as to combine with the assembled organic molecules. If this step is omitted, the subsequent molecular assembly cannot be completed.

[0015] In some embodiments, the concentration of the 3-aminopropyltrimethoxysilane solution is 2 to 5 mg / L. The amination-treated molecule is equivalent to a linker, which can bind to the hydroxyl-OH on the surface of the sample after oxidation treatment (such as the three-OH in the APTMS molecule, which can better bind to the-OH on the surface of the sample), and on the other hand, the amino-NH2 can bind to the negatively charged functional groups in the assembled molecules, such as the carboxyl-COOH in the heparin molecule, thereby improving the binding force between the subsequent assembled molecules and the sample surface.

[0016] In some embodiments, the concentration of the polyethyleneimine solution is 2 to 5 mg / L.

[0017] In some embodiments, during the amination process, the soaking time is 0.5 to 2 hours.

[0018] In some embodiments, the drug is at least one of heparin and chondroitin sulfate.

[0019] In some embodiments, the alternating soaking times is 5-20 times, and each soaking lasts for 1 to 1.5 hours.

[0020] In some embodiments, in the silane solution, the volume ratio of silane, ethanol, and water is 3:10-15:20-25. The role of the loaded silane coating is mainly to slow down the release of the loaded drug molecules. Through the drug sustained release experiment, it can be seen that the heparin release of the sample without the silane coating on the surface reaches the maximum value at 200 hours; after the silane coating is loaded, the heparin release increases with time until the release reaches the maximum value after 400 hours. In addition, the electrochemical test results show that compared with the sample without the silane coating, the current density of the sample loaded with the silane coating is reduced by an order of magnitude, and the impedance value increases by nearly 100 times, which slows down the degradation rate of the sample.

[0021] More specifically, it includes:

[0022] 1. Surface cleaning: Grind the surface of the zinc-based material with sandpaper, clean the sample surface with acetone, alcohol, and deionized water, and blow dry for later use;

[0023] 2. Surface oxidation: Soak the alloy sheet in NaCl solution, take it out after a period of time, clean it, and blow it dry;

[0024] 3. Surface amination: fully dissolve 3-aminopropyltrimethoxysilane (APTMS) or polyethyleneimine (PEI) in deionized water, and immerse the zinc alloy sheet in the solution for a period of time to make the surface have amino groups.

[0025] 4. Layer-by-layer assembly: Dissolve organic and inorganic molecules with positive and negative charges and certain functions to a certain concentration. Soak the amino zinc-based material alternately in solutions with positive and negative charged molecules, take it out after soaking for a period of time, and blow it dry until the number of alternating soakings reaches the required number. Organic molecules with negative charges, such as chitosan, have antibacterial properties; organic molecules with positive charges, such as heparin, have anticoagulant effects, and silver ions have antibacterial properties.

[0026] 5. Silane coating: Dissolve silane in water or an organic solvent to prepare a silane solution of a certain concentration. Soak the zinc material after layer-by-layer assembly in the silane solution for a certain period of time, and dry it in an oven for a period of time to prepare a silane coating.

[0027] The second aspect of the present invention provides a zinc alloy implant having a surface drug sustained-release coating prepared by the above method.

[0028] The third aspect of the present invention provides the use of the above-mentioned zinc alloy implant with surface drug sustained-release coating in the preparation of medical stents.

[0029] Beneficial effects of the present invention

[0030] (1) The present invention provides a method for preparing a functionalized coating on the surface of a zinc-based implant, that is, preparing a composite coating on the surface of the implant by layer-by-layer assembly technology, and the preparation method is safe, simple and easy to operate;

[0031] (2) The present invention can assemble organic and inorganic molecules with certain functions according to needs, so that the functionalized coating has the functions of anticoagulation, anti-inflammation, antibacterial, corrosion resistance, and biodegradability, thereby improving the biocompatibility of the implant and promoting uniform corrosion.

[0032] (3) The surface of the functionalized coating of the present invention is covered with a silicone coating, which can be slowly degraded and can achieve sustained release of drugs.

[0033] (4) The preparation method of the present invention is simple, practical and easy to promote. DETAILED DESCRIPTION

[0034] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0035] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0036] Embodiment 1:

[0037] ① Sample preparation: Cut the purchased pure zinc (purity 99.99%) plate into square pieces with a size of 10mm*10mm and a thickness of 2mm, polish it with sandpaper, clean the sample surface with acetone, alcohol and deionized water, and blow dry it for later use;

[0038] ② Surface oxidation: Soak the alloy sheet in a 0.9% NaCl solution, take it out after 24 hours, wash it, and blow it dry;

[0039] ③ Surface amination: Dissolve 3-aminopropyltrimethoxysilane (APTMS) in deionized water (concentration is 2 mg / L). Soak the zinc alloy sheet in the APTMS solution for 2 hours to make the surface have amino groups;

[0040] ④ Layer-by-layer assembly: Dissolve low molecular weight heparin (HP) in water (concentration of 2 mg / mL), soak pure zinc in HP solution, take it out after 1 hour, and blow dry; dissolve chitosan (CS) in acetic acid solution (concentration of 5 mg / mL), soak the amino sample in CS solution, take it out after 1 hour, and blow dry. At this time, the coating on the surface of pure zinc is marked as (HP / CS)1. After that, the sample is alternately immersed in CS and HP solutions to prepare (HP / CS) n Coating (n=5, 10, 20, is the number of alternating immersions).

[0041] ⑤ Silane coating: Mix methyltrimethoxysilane, ethanol and water in a volume ratio of 3:10:20, and stir thoroughly for 20 minutes in a water bath at 40°C. Soak the pure zinc sample with the assembled coating in this solution for 2 hours, then wash the surface with ethanol, place it in an oven at 120°C for 2 hours and then take it out. The drug sustained-release coating with anticoagulant, antibacterial and biocompatible properties on the surface of pure zinc is prepared.

[0042] Embodiment 2:

[0043] Steps ① and ② are the same as in Example 1;

[0044] ③ Surface amination: Prepare a 5 g / L polyethyleneimine (PEI) solution, immerse the prepared pure zinc sample in this solution for 30 min, and obtain a sample with a positive charge on the surface;

[0045] ④ Layer-by-layer assembly: Prepare polyacrylic acid (PAA) and gentamicin sulfate (GS) solutions with a concentration of 1 g / L respectively, and adjust the pH of the PAA solution to about 7.0. Soak the samples prepared in ③ in PAA and GS solutions for 5 minutes in turn, take them out, rinse them with deionized water and blow dry. This is one cycle, and the coating on the pure zinc surface is marked as (PAA / GS)1. After that, alternately immerse the samples in PAA and GS solutions until 20 cycles are completed, and the coating on the sample surface is marked as (PAA / GS) 20 .

[0046] Step ⑤ is the same as in Example 1. The preparation of the drug sustained-release coating on the surface of pure zinc with antibacterial and biocompatibility is completed.

[0047] Embodiment 3:

[0048] The pure zinc sample in step 1 was replaced with a Zn-0.8Li alloy, and the remaining steps were the same as in Example 2. A drug sustained-release coating with antibacterial and biocompatible properties was prepared on the surface of the Zn-0.8Li alloy.

[0049] Comparative Example 1

[0050] The difference from Example 1 is that no oxidation treatment is performed and subsequent molecular assembly cannot be completed.

[0051] Comparative Example 2

[0052] The difference from Example 1 is that no amination treatment is performed, which is not conducive to completing the subsequent molecular assembly.

[0053] Comparative Example 3

[0054] The difference from Example 1 is that heparin was not loaded.

[0055] The platelet adhesion experiment showed that the number of platelets adhering to the surface of the sample without heparin loading was large and aggregation occurred; while on the surface of the sample loaded with heparin, the number of platelets was significantly reduced to a few and no aggregation occurred.

[0056] Comparative Example 4

[0057] The difference from Example 1 is that no silane coating is supported.

[0058] The drug release experiment showed that the heparin release of the sample without silane coating reached the highest value at 200 hours; after loading the silane coating, the heparin release increased over time until it reached the highest value after 400 hours. In addition, the electrochemical test results showed that compared with the sample without silane coating, the current density of the sample with silane coating decreased by an order of magnitude, and the impedance value increased by nearly 100 times, which slowed down the degradation rate of the sample.

[0059] Table 1

[0060]

[0061]

[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a drug sustained-release coating on the surface of a zinc alloy implant, characterized in that: include: The zinc-based material is surface cleaned and placed in a salt solution for oxidation; The salt solution is a NaCl solution with a mass fraction of 0.9% to 1.2%; The oxidized zinc-based material is immersed in a 3-aminopropyltrimethoxysilane or polyethyleneimine solution to obtain an amino-modified zinc-based material; The aminated zinc-based material is alternately immersed in solutions with positively charged and negatively charged molecules for multiple times to obtain a zinc-based material with an assembled coating; The zinc-based material with the assembly coating is immersed in a methyltrimethoxysilane solution to obtain; In the methyltrimethoxysilane solution, the volume ratio of methyltrimethoxysilane, ethanol and water is 3:10-15:20-25; Wherein, the positively charged molecule is at least one of chitosan, polyethyleneimine, polyurethane, lysine, and arginine; The negatively charged molecule is at least one of silk fibroin, polypeptide, sodium hyaluronate, sodium alginate, polyacrylic acid and drugs.

2. The method for preparing the drug sustained-release coating on the surface of zinc alloy implant according to claim 1, characterized in that: The concentration of the 3-aminopropyltrimethoxysilane solution is 2-5 mg / L.

3. The method for preparing the drug sustained-release coating on the surface of zinc alloy implant according to claim 1, characterized in that: The concentration of the polyethyleneimine solution is 2-5 mg / L.

4. The method for preparing the drug sustained-release coating on the surface of zinc alloy implant according to claim 1, characterized in that: During the amination process, the soaking time is 0.5 to 2 hours.

5. The method for preparing the drug sustained-release coating on the surface of zinc alloy implant according to claim 1, characterized in that: The drug is at least one of heparin and chondroitin sulfate.

6. The method for preparing the drug sustained-release coating on the surface of zinc alloy implant according to claim 1, characterized in that: The number of alternating soaking times is 5-20 times, and each soaking time is 1 to 1.5 hours.

7. A zinc alloy implant having a surface drug sustained-release coating prepared by the method according to any one of claims 1 to 6.

8. Use of the zinc alloy implant with a surface drug sustained-release coating as claimed in claim 7 in the preparation of a medical stent.

Citation Information

Patent Citations

  • Controllable fully-degradable biomedical materials and preparation method thereof

    CN103272753A

  • Zinc alloy vascular stent material having ultra-high-flexible coating layer with drug sustained-release function

    CN110180038A

  • Drug sustained-release medical device and preparation method thereof

    CN116966402A

  • Method of preparing anticoagulant biological material using electrostatic self-assembling

    CN1448189A